Identification of RS266729 single nucleotide polymorphism in adiponectin promoter region Gene among diabetic patients attending Murtala Muhammad Specialist Hospital Kano State - Auwal Muhammad Abdullahi; Yahuza Gimba Muhammed; Muhammad Mahe Mukhtar; Jamila Sani; Muhammad Alhassan Wudil; Nasiru Abdullahi (Academy Publishing Center, 2024)
Type two diabetes is associated with adiponectin, which possesses characteristics that makes it sensitive to insulin. The study's aim was to identify the association of Rs266729 polymorphism  in patients attending Murtala Muhammad Specialist Hospital Kano State. Blood sample was obtained from twenty seven (27) participants. DNA was extracted, followed by Polymerase Chain Reaction (PCR) of AdipQ gene promoter region. The PCR product was sequenced to identify mutation. Result from this study identify that, the the distribution of the minor allele G (OR = 6.88, P = 0.012698) of rs266729 polymorphism was found to be associated with an increased risk of T2D compared to control group. The genetic model form of association showed that, the homozygous genotype (GG) and heterozygous genotype (CG) of rs266729 polymorphism were significantly associated with BMI, waist circumference and waist hip ratio  under the codominant and  dominant genetic models. Present study discovered that the minor allele G of rs266729 constitute a risk factor for the development of type two diabetes mellitus in patients attending Murtala Muhammad Specialist Hospital Kano State.   Received: 19 February 2024 Accepted: 15 April 2024 Published: 23 May 2024